Analisis Peramalan Permintaan dan Persediaan Produk Baut Menggunakan Metode Time Series dan Safety Stock di PT. DRA Component Persada - Zulziar, Marjuki; Purnomo, Andi; Sarwoko, Wanto (Universitas Pamulang, 2025)
DRA Component Persada is a manufacturing company that produces various types of bolts. The main problem faced by companies is unstable fluctuations in demand, so that sometimes there is a buildup of stock or a shortage of inventory in the warehouse. The aim of this research is to analyze forecasting demand and supply of bolt products at PT. Dra Component Persada. To overcome this, this research uses the Time Series forecasting method which includes Moving Average, Weight Moving Average, and Exponential Smoothing to determine future demand and the Safety Stock method to overcome demand instability. From the results of calculations carried out by the author, the Exponential Smoothing model with a = 0.2 is the optimal forecasting model with the smallest error level, namely with a Mean Absolute Deviation (MAD) of 1,218,085, a Mean Squared Error (MSE) of 1,886,215,000,000 , and the Mean Absolute Percentage Error (MAPE) is 2.74%. The forecast for the coming period is predicted to be 4,440,637 pcs, while the safety stock required is 393,215 pcs with a service level of 95%. It is hoped that the application of forecasting and safety stock methods can increase stock management efficiency and better meet customer needs.